Answer:
1. Multiply by 3
2. Multiply by 1/3
Explanation:
6x - 3y = 3
-2x + y = -14
1. In order to eliminate the x-terms, they would both have to equal the same number with opposite signs (positive and negative). Since we are only touching the second equation, how can we get from 2 to 6? We can multiply 2 by 3 to get to 6 (negative 6 in the end.) This would result as follows:
6x - 3y = 3
-6x + 3y = 42
2. In order to eliminate the y-terns through multiplying with the first equation, we have to figure out how to make 3y into 1y. We can do this by adding its reciprocal, 1/3. 1/3 × 3 = 1. This would result as follows:
2x - y = 1